Opportunities and challenges for polymer science using synchrotron-based infrared spectroscopy. (August 2016) - Ellis, Gary J.; Martin, Michael C.
Graphical abstract: Highlights: The nature of synchrotron-based infrared microspectroscopy is outlined. Several applications in the field of polymer materials science are described. Recent developments in experimental techniques relevant to polymer science are presented. Cutting-edge 2D and 3D imaging, spectro-micro-tomography and nanospectroscopy are shown. Dynamics, special environments and high pressure techniques are discussed. Abstract: Many breakthrough advances that are often at the cutting edge of technological development take place at synchrotron facilities. In the case of IR spectroscopy, the last decade has seen important developments in infrared instrumentation incorporated to and developed at synchrotron facilities to take advantages of the characteristics of the bright synchrotron source. In this feature article we describe the origin and nature of synchrotron infrared microspectroscopy, highlighting some of the key developments that will make a future impact in the study of macromolecular materials, and illustrating several applications in the area of polymer science.